Islamic performance index on firm performance: A literary overview - Noor, Amira; ‘Ana, Naahrooq; Abdullah, Sa’if (Asian Journal of Economics and Business Management, 2025)
The Islamicity Performance Index (IPI) serves as a critical measure in evaluating the financial and ethical performance of Islamic banks. This study presents a comprehensive literature review of existing research on IPI, highlighting its strengths, limitations, and its impact on profitability, firm value, and Maqāsid al-Sharī‘ah compliance. Findings indicate that while IPI has a positive influence on firm value and financial performance in certain contexts, inconsistencies arise due to a trade-off between ethical obligations and profitability. Some financial ratios within IPI, such as the Profit Sharing Ratio, exhibit no significant effect on profitability, while others, such as the Equitable Distribution Ratio, show a positive impact over time. Additionally, evidence suggests that many Islamic banks prioritize financial gains over ethical and social considerations, creating challenges in fully integrating Maqāsid al-Sharī‘ah into banking operations. This study underscores the need for refining IPI methodologies to ensure that Islamic banks uphold both financial sustainability and Islamic ethical values. The role of corporate governance, regulatory frameworks, and standardization in enhancing IPI’s effectiveness remains crucial. Future research should explore ways to enhance IPI’s applicability by incorporating broader measures of social and ethical responsibility. A balanced approach is necessary to bridge the gap between financial performance and Islamic principles, ultimately strengthening the credibility of Islamic banking institutions. This study contributes to the ongoing discourse on Islamic banking performance evaluation, offering insights into improving the alignment between profitability and ethical considerations.